Alkylthiol-enabled Se powder dissolving for phosphine-free synthesis of highly emissive, large-sized and spherical Mn-doped ZnSeS nanocrystals. Issue 71 (19th September 2017) - Ke, Bao; Bai, Xianwei; Wang, Rongkai; Shen, Yayun; Cai, Chunxiao; Bai, Kun; Zeng, Ruosheng; Zou, Bingsuo; Chen, Zhencheng
Abstract : The enhanced dissolution of Se without organo-phosphines is a key issue in the synthesis of oil-soluble selenide nanocrystals. Abstract : The enhanced dissolution of Se without organo-phosphines is a key issue in the synthesis of oil-soluble selenide nanocrystals. In this article, the dissolution of Se powder was greatly promoted by addition of 1-dodecanethiol at 200–220 °C. This Se precursor was of high reactivity and was suitable for the preparation of Se semiconductor nanocrystals. With this greener Se precursor, approximately spherical and large-sized Mn:ZnSeS quantum dots (QDs) could be prepared after multiple injections of the Zn precursor, and the size of Mn:ZnSeS can reach over 8.5 nm after the tenth injection of the Zn precursor. The preparation of this novel selenium precursor is simple and convenient, and provides a meaningful method for the synthesis and application of other selenium nanocrystals.